Prescription pattern among patients having mild to moderate bronchial asthma using metered dose inhaler and dry powder inhaler in tertiary hospital in western india - Akhoon, Neha; Brashier, D. B. S. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Bronchial asthma is a syndrome characterized by airflow obstruction that manifests as shortness of breath, wheezing and cough. The treatment is tailored according to the severity of the disease. The drugs used for treatment of bronchial asthma include inhaled corticosteroids, beta-2 agonists, methylxanthines, leukotriene antagonists and mast cell stabilizers. Despite the availability of all these drugs, which are recommended for the treatment, not every patient achieves complete control of the disease. The reason behind this could be irrational prescribing of drugs for the treatment and errors in the technique of using inhaler devices. Though rational prescribing of drugs and correct technique for the use of inhaler can be improved by proper training of target population, but there is paucity of such data in our country. Methods: This study was planned to monitor prescription pattern and errors in use of inhalation devices, in patients diagnosed as cases of mild to moderate bronchial asthma, attending Out Patient Department (OPD) of respiratory medicine of a tertiary hospital. A total of 207 patients were recruited and their prescription pattern and inhalation technique were assessed. Results: The study showed that inhaled short acting β2-agonists and inhaled corticosteroids were the most commonly used drug groups, which were prescribed to all the patients in the study, followed by long acting β2-agonists, leukotriene antagonists and methylxanthines in decreasing order. Conclusions: As a conclusion, the treating physicians were prescribing according to the laid down guidelines. It is concluded that such studies should be periodically done to ensure the adherence to the treatment guidelines.